Volatility Shocks and Investment Behavior - Christoph Huber; Jürgen Huber; Michael Kirchler (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2021)
We investigate how volatility shocks affect investors' risk-taking, risk perception and forecasts. We run artefactual field experiments with two participant pools (finance professionals and students), differing in (i) the direction of the shock (down, up, or a neutral case) and (ii) the presentation format of the time series (prices or returns). Professionals\~O investments are negatively associated with the price change and performance of the stock and their perceived risk increases to a similar extent following shocks of all directions. Students' risk perception, in contrast, is more closely related to the frequency of negative returns rather than an increase in volatility.
Keywords: C91; G11; G41; 330; Risk perception; experimental finance; finance professionals; volatility shocks